Effects of stimulant pH, light and soil moisture on Orobanche solmsii seed germination - Bista, Anjana (Ecoprint: An International Journal of Ecology, 2016)
In order to investigate effect of soil moisture, Orobanche seeds were pre-conditioned in three different soil moisture conditions. The germination percentage was found to be highest (48.31%) in normal soil moisture condition and lowest (4.6%) in flooded soil moisture condition. This indicates that Orobanche seeds are unable to survive for a long period in water logged conditions. In response to stimulant pH, Orobanche solmsii seeds showed significantly a high germination percentage (65.27%) at pH value 6.5 and it declined progressively with the increase of acidic and alkaline conditions. However, seeds appeared to be more sensitive to alkaline rather than acidic condition. The study of effect of light showed that exposure of seeds to continuous light during pre and postconditioning period inhibited seed germination. The inhibition was more effective when seeds were exposed to light during post conditioning phase rather than during pre- conditioning phase. ECOPRINT 22: 57-62, 2015